The Labor Market Effects of State and Local Expansions of the Earned Income Tax Credit - Mondal, Sunita (Journal of Applied Business and Economics, 2021)
This study analyzes the labor market impact of state and local supplements to the federal Earned Income Tax Credit (EITC) program. Using Current Population Survey data from 1984 to 2020, I examine the differential impact of the state and local government supplements of the EITC on the labor force participation rates of married women. I examine whether the substantial expansions in the EITC program created by these supplements are an effective means of providing work incentives. In particular, do states and local counties with an EITC supplement witness higher female labor force participation rates? Exploiting variation in the policy over time both across states and within states between different demographic groups, I analyze whether the EITC supplements have raised labor supply among single women, and whether such differences exist in the labor supply of married women.